Faktor Keuangan Dan Non Keuangan Pada Opini Going Concern(Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2013) - Aliah, Miskiyatul; , Drs. Suyatmin Waskito Adi, M.Si (2015)
The purpose of this study was to analyze whether the financial factors that include profitability ratio, leverage ratio, ratio of market prices, affecting the going concern opinion on manufacturing companies and analyze whether the non-financial factors that include the auditor's reputation, Tenure, Disclosure, The size of the company affects the company's going concern opinion manufacturing. The sample in this study were selected using purposive sampling approach. Sample selection criteria as follows: Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) in 2009 until 2013. The required data is available to complete and publish the financial statements have been audited by an independent auditor from 2009 to 2013. Experiencing negative net income at least two periods of the financial statements during the observation period (2009-2013). Negative net income is used to indicate Events troubled financial companies and has a tendency to accept the going concern audit opinion. Based on the analysis using logistic test known variable profitability (ROA), variable leverage (DER), the auditor's reputation variable, the variable tenure, disclosure variable, the variable size of the company does not affect the going concern audit opinion. Market price variable (MBR) affect the going concern audit opinion.